Woman and shariah court: A study of Malaysia and Indonesia - Wan Muhammad, Ramizah (MUK Publications, 2015)
This paper examines the status of woman as a shari‘ah court judge according to the classical Muslim jurists. It begins with the historical background of the status of woman before and after the advent of Islam. In the Holy Qur’an there is a chapter on women which shows that the women have a special place in Shari‘ah. However, in the case of a woman judge, there are differing juristic views, but their views are open to interpretation. The paper makes such attempt to justify the notion that a woman can be appointed as a judge of the shari‘ah court. The paper also looks into the contemporary situation in Malaysia and Indonesia, where Islam is the religion of the majority of the population, and it is recognized as the religion of these states. The function of the government that looks after the interests of the community in the absence of the original legal rulings in the Divine revelations is also discussed. The paper discusses the importance of Shari‘ah Court as an institution to dispense justice regardless of who the judge is. Most of the time, the culture and norms of a certain community are the impediments to the success of each country and not simply of one’s belief.